Music & Well-being – Music as Integrative Experience - Boyce, June (Journal of Urban Culture Research, 2014)
This article will examine the power of the liminal space as a transformative experience. It will also examine a holistic model of the musical experience that brings together the environmental, the expressive, the intellectual, the social and the intuitive within its very nature. It will link this with contemporary developments in the area of spirituality/liminality. It will illustrate this from three projects - a Singing for Well-being choir, the Space for Peace event in Winchester Cathedral and a local community pageant. It will draw on the work of John Dewey, Christopher Small, Victor Turner, Estelle Jorgensen, Heidi Westerlund and Richard Shusterman.